La agroclimatología: instrumento de planificación agrícola - Hernández Navarro, María Luz (Geographicalia, 2017)
This paper analyses agroclimatology as an effective instrument which can be taken as a decisive, objective criterium for agricultural planning. Its application contributes to ensure the efficacy of cultivation planning, by minimising risks and maximising both the quantity and the quality of the crops. This analysis includes a study of the objectives and applications of this science, as well as the sources (both periodical and non-periodical) of information, and the different climatic parameters. It also includes a list of bibliographical references. As a conclusion, it shows the necessity of shaping a bank of agroclimatic data and of carrying out coordinated research projects of climatology and agriculture, so asto face those specific needs which cannot be solved by means of the existing techniques.
Keywords: Agroclimatology; agricultural planning; temperature; precipitation; hydric balance.